1994
DOI: 10.1109/20.334301
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel signal processing for multiple-head digital magnetic recording

Abstract: This paper analyzes the performance of a multiplehead, digital, magnetic recording system using multichannel signal processing theory. A multi-input, multi-output (MIMO) channel that models the multiple-head recording process provides the basis for this analysis. This model characterizes the write process, the read process and both electronics and media noise. In particular, the model accounts for side fringing between a read head and adjacent tracks; side fringing is a major cause of intertrack interference t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Previous work that looked at this for longitudinal recording channels include Refs. [1][2][3][4][5][6][7][8][9][10]. Multi-track recording codes that control the type of adjacent transition can significantly affect error performance in the presence of ATI [11].…”
Section: Channel Model For Constructive Iti Codementioning
confidence: 99%
“…Previous work that looked at this for longitudinal recording channels include Refs. [1][2][3][4][5][6][7][8][9][10]. Multi-track recording codes that control the type of adjacent transition can significantly affect error performance in the presence of ATI [11].…”
Section: Channel Model For Constructive Iti Codementioning
confidence: 99%
“…Theoretical investigations have revealed that multi-head detection for multi-track partial response (PR) recording channels is capable of increasing storage density and combating intertrack interference (ITI) in high-density systems much better than single-head detection [1][2]. Maximum-likelihood sequence detection (MLSD) is an optimal approach [3] but its computational complexity grows exponentially with both the partial response order and the total number of tracks due to the use of the multi-dimensional Viterbi algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…(iii) Improvements in system performance: Servos, track following, multiple head configurations [9][10].…”
Section: The Importance Of Signal Processingmentioning
confidence: 99%